Digital Leadership and Supply Chain Adaptability: Pathways to sustainable Supply Chain Performance - Zafar Iqbal; Dr. Habib Ullah; Dr. Kalsoom Akhtar (Journal of Religion and Society, 2026)
The study explores how digital leadership (DL) influences sustainable supply chain performance (SSCP) and supply chain adaptability (SCA) as a mediating construct. Based on a sample of 250 pharmaceutical distribution firms’ managers and executives of Bahawalpur, Pakistan. The study uses the quantitative method of analyzing structural associations among the constructs with SmartPLS. The results show that DL has a significant impact on SSCP and SCA, and the latter has a positive influence on SSCP. Mediation analysis supports the fact that SCA is a partial mediating variable between the two variables, DL and SSCP, which implies that adaptability is a significant yet not the only mechanism by which digital leadership would produce favorable sustainability outcomes. The findings can be added to the expanding literature on the concept of digital leadership and sustainable supply chain performance as they show the dual significance of operational flexibility and leadership vision. In practice, the paper provides recommendations to managers who want to integrate sustainability into the supply chain management, highlight the importance of developing digital leadership skills, and utilize newer technologies, including cloud-based analytics, IoT, and blockchain. Hypothetically, the study contributes to the knowledge of digital leadership and adaptability from the perspective of sustainability and preconditions further studies that will involve contextual, longitudinal, and cross-sector comparisons. Keywords: Digital Leadership, Supply Chain Adaptability, Sustainable Supply Chain Performance, Pharmaceutical Distributions